2014
DOI: 10.1182/blood-2013-12-544569
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of a physiologically relevant model of lymphocyte migration in chronic lymphocytic leukemia

Abstract: Key Points• We have developed a novel in vitro system to model how shear force and transient interaction with endothelial cells alter chronic lymphocytic leukemia cell phenotype and behavior.• We have used our model to investigate chronic lymphocytic leukemia cell migration and have determined the critical role for integrin a4b1 in this process.There is growing evidence that lymphocyte trafficking contributes to the clinical course of chronic lymphocytic leukemia (CLL), but to date, only static in vitro cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 45 publications
(54 reference statements)
4
30
0
Order By: Relevance
“…In keeping with our previous report, 23 a small percentage of CLL cells migrated into the EVS after 48 hours (1.37% 6 2.32%). Compared with CLL cells remaining in the circulating compartment, migrated cells showed lower expression of CXCR4 (P 5 .0058), as well as increased expression of CD49d (P , .0002), CD38 (P , .0001), HLA-DR (P 5 .0002), CD5 (P 5 .0044), CD80 (P , .0001), CD86 (P 5 .0006), and CD69 (P 5 .0007) ( Figure 3B).…”
Section: Functional Differences Of Ln Vs Pb-cll Cells 567supporting
confidence: 93%
See 4 more Smart Citations
“…In keeping with our previous report, 23 a small percentage of CLL cells migrated into the EVS after 48 hours (1.37% 6 2.32%). Compared with CLL cells remaining in the circulating compartment, migrated cells showed lower expression of CXCR4 (P 5 .0058), as well as increased expression of CD49d (P , .0002), CD38 (P , .0001), HLA-DR (P 5 .0002), CD5 (P 5 .0044), CD80 (P , .0001), CD86 (P 5 .0006), and CD69 (P 5 .0007) ( Figure 3B).…”
Section: Functional Differences Of Ln Vs Pb-cll Cells 567supporting
confidence: 93%
“…It has been previously shown that CD49d expression identifies CLL cells that have an increased capacity to undergo TEM 12,23 and interestingly, it is also a co-stimulatory molecule. 26 In order to investigate whether there is a link between migration and costimulation in CLL, we correlated the expression of CD49d with a variety of activation and co-stimulatory molecules in the LN and PB of patients with CLL, and in the circulating and extravascular compartment of the in vitro circulation system.…”
Section: D)mentioning
confidence: 99%
See 3 more Smart Citations